Sistem Informasi Antrean Apotek Rumah Sakit Menggunakan Metode Prototype (Studi Kasus RSUD Praya) - Lalu Novalino Roasta Ramadhan; Moh. Ali Albar; Nadiyasari Agitha (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2021)
In the waiting room of the hospital pharmacy, over queues often occur. It is not efficient because it time consuming or other activities just for waiting. Thus, we need a system that can be used by patients to see the queue wherever it is. In this final project, a hospital pharmacy queue information system is designed. This information system is designed on a web basis so that patients can access through all platforms which will be used by patients to make it easier to see the queue. In making the system, the prototype method is used so that it can be evaluated periodically when finding problems in the system. The advantage is the system can be fixed immediately if a bug is found. In this system, there are two users, consist of patients and pharmacy staff, this system also makes it easier for patients to predict queues because patients can see the queue status and drug status (concocted or non-concocted) at the pharmacy. So the patients can leave the waiting room when the queues are congested and return to the waiting room when they are about to have their turn. The results of this system enable RSUD Praya to saw the average length of queues for concoctions and non-concoctions at the Praya Hospital pharmacy per month. So that it can measure the service level whether it meets the SOP that has been determined or not.